A new giant species of Arthroleptis (Amphibia: Anura: Arthroleptidae) from the Krokosua Hills Forest Reserve, south-western Ghana - Ernst, Raffael; Agyei, Alex C.; Rödel, Mark-Oliver (Zootaxa, 2008)
We describe a new giant species of Arthroleptis from the eastern part of the Upper Guinean rain forest, West Africa. This species from the Krokosua Hills Forest Reserve, south-western Ghana is the largest member of the genus from West Africa. It differs from all known West African Arthroleptis by its large size, its peculiar coloration and a number of morphological characters, such as e.g. an extremely broad head. Arthroleptis krokosua sp. nov. is most similar to large members of the genus from East and Central Africa, particularly A. variabilis and A. adolfifriederici from which it differs in lateral and ventral colouration patterns, larger size (> 43 mm), as well as head shape (heads width / snout-vent length: 0.45; 0.40 in A. variabilis and A. adolfifriederici). Genetic divergence in 550 bp of 16S rRNA was 4.97–5.14 % between the new species and A. variabilis. The new species seems to have no apparent affiliations to any other West African member of the genus. All other West African Arthroleptis are much smaller in size and differ in body shape.